Penggunaan Framework Cobit 2019 dalam Evaluasi Tata Kelola Teknologi Informasi - Senna Kristiawan Gouwnalan; Andeka Rocky Tanaamah (Maranatha University Press, 2023)
Kospin Jasa is a savings and loan cooperative founded in the 1970s by several small entrepreneurs. It is established to overcome difficulties in obtaining capital loans because businesses are still managed traditionally. Therefore, on December 13, 1973, Mr. HA Djuanaid (Alm), a national cooperative leader, met and agreed to establish a savings and loan cooperative. With the rapid development of information technology, companies/organizations have the opportunity to increase productivity. The application of information technology supports increased competitiveness with competitors. Management of information technology should then be audited. Typically, the necessary controls are provided by COBIT. This article is here to discuss information technology management which impacts cost overruns. This paper collects data through library research using qualitative methods. The results obtained are in the form of an IT governance design plan and are taken from COBIT 2019